Operational and performance issues of a CBQ router. - Risso, Fulvio (Computer communication review.)
The use of scheduling mechanisms like Class Based Queueing (CBQ) is expected to play a key role in next generation multiservice IP networks. In this paper we attempt an experimental evaluation of ALTQ/CBQ demonstrating its sensitivity to a wide range of parameters and link layer driver design issues. We pay attention to several CBQ internal parameters that affect performance drastically and particularly to "borrowing", a key feature for flexible and efficient link sharing. We are also investigating cases where the link sharing rules are violated, explaining and correcting these effects wheneverpossible. Finally we evaluate CBQ performance and make suggestions for effective deployment in real networks.